Expanding the phenotype of HNRNPU‐related neurodevelopmental disorder with emphasis on seizure phenotype and review of literature. Issue 5 (9th February 2022) - Taylor, James; Spiller, Michael; Ranguin, Kara; Vitobello, Antonio; Philippe, Christophe; Bruel, Ange‐Line; Cappuccio, Gerarda; Brunetti‐Pierri, Nicola; Willems, Marjolaine; Isidor, Bertrand; Park, Kristen; Balasubramanian, Meena
Abstract: Pathogenic variants in heterogeneous nuclear ribonucleoprotein U ( HNRNPU) results in a novel neurodevelopmental disorder recently delineated. Here, we report on 17 previously unpublished patients carrying HNRNPU pathogenic variants. All patients were found to harbor de novo loss‐of‐function variants except for one individual where the inheritance could not be determined, as a parent was unavailable for testing. All patients had seizures which started in early childhood, global developmental delay, intellectual disability, and dysmorphic features. In addition, hypotonia, behavioral abnormalities (such as autistic features, aggression, anxiety, and obsessive–compulsive behaviors), and cardiac (septal defects) and/or brain abnormalities (ventriculomegaly and corpus callosum thinning/agenesis) were frequently observed. We have noted four recurrent variants in the literature (c.1089G>A p.(Trp363*), c.706_707del p.(Glu236Thrfs*6), c.847_857del p.(Phe283Serfs*5), and c.1681dels p.(Gln561Serfs*45)).